2018
DOI: 10.1371/journal.pone.0199569
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of insect pest distribution as influenced by elevation: Combining field observations and temperature-dependent development models for the coffee stink bug, Antestiopsis thunbergii (Gmelin)

Abstract: The antestia bug, Antestiopsis thunbergii (Gmelin 1790) is a major pest of Arabica coffee in Africa. The bug prefers coffee at the highest elevations, contrary to other major pests. The objectives of this study were to describe the relationship between A. thunbergii populations and elevation, to elucidate this relationship using our knowledge of the pest thermal biology and to predict the pest distribution under climate warming. Antestiopsis thunbergii population density was assessed in 24 coffee farms located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…Numerous studies have demonstrated the influence that temperature exerts on the development and survival of insects 7,14,39 . Yet, because the response of insects to temperature is species‐specific, studies about the effect of temperature on insect biology are still relevant, particularly for agricultural and forest pests due to their application in pest management and prediction of species distributions under current and projected climate conditions using mechanistic or hybrid models 8,40–42 . In this context, knowledge of the thermal thresholds of insect pests may help in understanding the risks of a given species spreading to regions outside its native range.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the influence that temperature exerts on the development and survival of insects 7,14,39 . Yet, because the response of insects to temperature is species‐specific, studies about the effect of temperature on insect biology are still relevant, particularly for agricultural and forest pests due to their application in pest management and prediction of species distributions under current and projected climate conditions using mechanistic or hybrid models 8,40–42 . In this context, knowledge of the thermal thresholds of insect pests may help in understanding the risks of a given species spreading to regions outside its native range.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the density of these insects and their herbivory, particularly on tree host species, are thought to decrease at higher elevations because of temperature constraints on herbivore development and reproduction [67][68][69]. However, in several studies, the opposite pattern or an intermediate optimum elevation for density and herbivory have been reported [70][71][72]. These discrepancies in phloeophagous as well as phyllophagous species emphasize the decisive role of host plant susceptibility as affected by e.g., water supply [54] and potentially of natural enemies [14] for herbivores in general.…”
Section: Effects Of Temperature On Bark Beetle Populationsmentioning
confidence: 99%
“…Although insects do not develop at a constant temperature in nature, development models obtained from laboratory studies provide useful information on their thermal biology, such as thermal thresholds. As such, they help understand and predict the pest distribution and population dynamics in plantations according to temperature (Tonnang et al, 2013;Azrag et al, 2018). To the best of our knowledge, the only study that adopted a similar approach for H. hampei is that of Jaramillo et al (2009).…”
Section: Temperature-dependent Development Modelsmentioning
confidence: 99%
“…As poikilotherm animals, insects depend primarily on the temperature of their environment to develop (Régnière et al ., 2012). Pest distribution and population dynamics, therefore, can be largely predicted by running temperature-dependent models of development (Tonnang et al ., 2013; Azrag et al ., 2018). These tools also provide standard life history traits such as temperature thresholds and thermal constant that characterize the relationships between insect development and temperature (Wagner et al ., 1991; Nielsen et al ., 2008; Azrag et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%